1991
DOI: 10.1007/bf00587820
|View full text |Cite
|
Sign up to set email alerts
|

Do arachnoid cysts grow?

Abstract: The volumes of intracranial arachnoid cysts were measured in 136 CT scans of 86 patients. Absolute and relative cyst size was calculated. Left hemisphere and middle cranial fossa location prevailed. A slight negative correlation of relative cyst size with age (r = -0.21, NS) disappeared when analysis was restricted to the adult age group (greater than or equal to 20 years). After the sample was divided into two groups according to relative cyst size (cysts less than mean volume vs cysts greater than mean volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The arachnoid cysts become symptomatic during childhood in about 70–90% [3,4,5,6,7,8]. Besides the theory of a congenital origin of these pathologic findings, reports also support the hypothesis of acquiring these arachnoid cysts due to mechanisms such as infection, trauma, pressure or CSF flow changes [9,10,11].…”
Section: Introductionmentioning
confidence: 79%
“…The arachnoid cysts become symptomatic during childhood in about 70–90% [3,4,5,6,7,8]. Besides the theory of a congenital origin of these pathologic findings, reports also support the hypothesis of acquiring these arachnoid cysts due to mechanisms such as infection, trauma, pressure or CSF flow changes [9,10,11].…”
Section: Introductionmentioning
confidence: 79%
“…The relevance of these observations is whether one would expect the temporal lobe to expand after successful treatment or not. Regardless of origin, several studies have shown that a large proportion of middle fossa arachnoid cysts enlarge with time [5, 6, 7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…The majority of these cysts occur in the middle cranial fossa. Large middle fossa arachnoid cysts are more likely to be symptomatic, and appear to have the highest risk of undergoing significant expansion [2]. There appears to be a male predominance for these lesions [4, 8, 11].…”
Section: Discussionmentioning
confidence: 99%
“…These are benign lesions that usually remain fairly stable in size. Despite this, between 60 and 80% become symptomatic [2]. Occasionally, intracystic hemorrhage occurs with or without preceding trauma [3].…”
Section: Introductionmentioning
confidence: 99%